Development of a Standardized Nutrient Matrix for Corn Distillers Dried Grains with Solubles - Waldroup, P.W.; Wang, Z.; Coto, C.; Cerrate, S.; Yan, F. (International Journal of Poultry Science, 2007)
The rapid increase in production of ethanol from corn and other grains has resulted in growing quantities of byproducts, primarily distillers dried grains with solubles (DDGS). The use of DDGS in poultry diets is not new, but the supply of product encourages the use of higher percentages than has typically been used in the past. As greater quantities are used in the diet, it becomes increasingly essential that accurate nutrient values be assigned to the product. This review attempts to summarize results from various laboratories to provide a nutrient matrix that can be used to evaluate the potential use of DDGS in poultry feeds.